DAMPAK SOSIAL PEMBANGUNAN JEMBATAN DESA KAMPUNG PANJANG AIRTIRIS KECAMATAN KAMPAR UTARA KABUPATEN KAMPAR - Fitrah Aini; Swiss Tantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Bridge infrastructure development coined positive impact and negative impact in the lives of the viage Kampung Panjang, the perceived impact the community with the construction of the bridge can be in many different forms. this study to determine the positive and negative impacts of development experienced by rural village kampung panjang, and, knowing the social impact of the construction of the bridge to changes in social status vertically and determine changes in social status due to the construction of a bridge or there are other factors. The population in this study is that people who live in the village Kampung Panjang Airtiris Kecamatan Kampar Utara Kabupaten Kampar totaling 366 families (households), the sampling technique with random samples taken 10% as many as 36 families. The method used is descriptive quantitative method with quantitative data analysis, research instruments used were questionnaires, interviews and documentation.These results indicate that the positive impact of the construction of the bridge at 61.11%, which can be seen from the smooth traffic, saving travel time, low levels of accidents, increase revenue, expand business opportunities, the smoothness of goods and services, the establishment of harmonious relations between villages, good social relations. The negative impact of the construction of the bridge at 38.89%, which can be seen from the demise of the services crossing (raft), the bridge is misused by teenagers, modern life, the depletion of local culture, a stranger out of the village, and it turns out that people's social status changes vertically changed since the construction of the bridge can be seen from the change in shape of the house, people's incomes rise, rising sense of pride, and changes in social status was changed is because the construction of the bridge was not due to other factors.Keywords: Social Impact, Bridge Construction, Social Change